Analysis of Spelling Error In Dissertation Based on the General Guideline for Indonesian Spelling (Pedoman Umum Ejaan Bahasa Indonesia) - Yakob, Muhammad; Asra, Surya (International Journal for Educational and Vocational Studies, 2019)
This study aims at describing and classifying forms of misspelling in dissertations based on General Guideline for Indonesian Spelling (Pedoman Umum Ejaan Bahasa Indonesia [PUEBI]). It is a descriptive qualitative study. The type of data obtained in this study is document text, consisting of primary data sourced from dissertation and secondary data sourced from related documents. Data collection is carried out by using text analysis, documentation, and recording techniques. The result of this research shows that spelling errors in dissertation include 10 errors of writing capital letter, 9 errors of writing italic, 14 errors of forming word, 5 errors of using full stop mark, 5 errors of using comma sign, 1 error of using colon sign, and 6 errors of using quotation mark. Maximum errors are in the use of punctuation and the word formation. Based on the result, it can be concluded that there are still many spelling errors in writing dissertation. Therefore, it needs more effort to understand the rules of writing, such as the use of standard words, PUEBI, capital letter, punctuation, and word formation to make a good writing, especially in writing dissertation.